PENGARUH BEAUTY VLOGGER DAN CELEBGRAM ENDORSER PADA BRAND IMAGE DAN DAMPAKNYA TERHADAP PURCHASE INTENTION PADA PRODUK MAKE OVER - admin, ILFIYANI ZIKRIE B1021161074 (Jurnal Manajemen Update, 2020)
ABSTRACTThis study aims to determine the effect of beauty vloggers and celebgram endorsers on brand image and its impact on purchase intention of Make Over products. This type of research uses an explanatory research approach with a quantitative approach. With the data collection method using a questionnaire with a sample of 100 respondents distributed online using the path analysis method. Based on the results of data analysis, it is concluded that beauty vlogger has a significant effect on brand image and purchase intention, celebgram endorser has a significant effect on brand image, celebgram endorser has not significant effect on purchase intention and brand image has a significant effect as a mediating variable between beauty vlogger and purchase intention.Â Keywords: Beauty Vlogger, Celebgram Endorser, Brand Image, Purchase Intention and Make Over.DAFTAR PUSTAKAAditya, Kadek Yoga & I Made Wardana. 2017. Peran Brand Equity Dalam Memediasi Pengaruh Word Of Mouth Terhadap Purchase intention. E-Jurnal Manajemen Unud, 6 (2), hal.830-856.Assael, Henry. 2001. Consumer Behavior 6th Edition. New York: Thomson-Learning.Chen, Jui-Lung & Dermawan, Apritika. 2020. The Influence of YouTube Beauty Vloggers on Indonesian Consumersâ€™ Purchase Intention of Local Cosmetic Products. International Journal of Business and Management; Vol. 15, No. 5Choi, G.Y. & Behm-Morawitz, E. 2017. Giving a new makeover to STEAM: Establishing youtube beauty gurus as digital literacy educators through messagges and effects on viewers, Computers ini Human Behavior, 73 : 80-91.Durianto, Darmadi . 2013. Strategi Menaklukan Pasar Melalui Riset Ekuitas dan Perilaku Merek (cet. ke-10). Jakarta: PT Gramedia Pustaka Utama.Ghozali, Imam. 2016. Structural Equation Modeling, Metode Alternatif dengan Partial Least Square (PLS). Edisi 4. Semarang : Badan Penerbit Universitas Diponegoro.Hardjanti, A., & Siswanto, H. 2014. Pengaruh dimensi endorser credibility dan brand credibility terhadap dimensi concumer-based brand equity. Jurnal iImiah Widya, 2(3), 42â€“50.Hassan, S., & Jamil, R. (2014). Influence of Celebrity Endorsement on Consumer Purchase Intention for Existing Products: A Comparative Study. Journal of Management Info, 4(1), 1-23.Huang, Shiu Li & Ku, Hsiou Hsuan. 2016. Brand Image Management for Nonprofit Organizations: Exploring The Relationships Between Websites, Brand Images and Donations. Journal of Electronic Commerce Research, Vol 17 no 1.Hutapea. 2016. Pengaruh Beauty Vlogger dan Brand Image: Survei Pengaruh Beauty Vlogger Sebagai Endorser Terhadap Brand Image The Body shop. Departemen Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik (Skripsi dipublikasikan) Universitas Gadjah Mada,YogyakartaJalilvand, Mohammad Reza & Samiei, Neda .2012. "The effect of electronic word of mouth on brand image and purchase intention: An empirical study in the automobile industry in Iran", Marketing Intelligence & Planning, Vol. 30 Issue: 4, pp.460-476Jung, Eun Lee & Watkins, Brandi. 2016. Youtube vloggers' influence on consumer luxury brand perceptions and intentions Journal of Business Research 69 5753â€“5760.Kotler, Philip & Kevin Lane Keller. 2016. Marketing Management, 15th Edition New Jersey: Pearson Pretice Hall, Inc.Nugroho, Adi Rifqi. 2013. Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Dengan Sistem Pre Order Secara Online (Studi Kasus Pada Online Shop Chopper Jersey). Semarang: Fakultas Ekonomika dan Bisnis Universitas Diponegoro.Orlando, Dillon. 2015. Analisa Pengaruh Brand Image dan Brand Awareness Terhadap Purchase Intention Sepeda Motor â€œKawasaki Ninja 250 Fiâ€. Jurnal Manajemen Pemasaran Petra. Vol. 3 No. 1 1-9.Pixability Company. 2014. Beauty on Youtube: How Youbube is radically transforming the beauty industry and what that means for brand. Diakses pada tanggal 18 Januari 2021 pukul 02:34 WIB https://www.pixability.comPutri, Maharani Nindiya & Listiani, Endri. 2018.Â  Electronic Word of Mouth (E-WOM) is Used by Beauty Vloggers and Its Effect on Purchase Intention. Journal of Management Communication Volume 4, No. 2.Rachmadi, K.R & Nurhajati. 2018. Pengaruh Vlogger Review Sebagai Celebrity Endorser Terhadap Purchase Intention dengan Brand Image Sebagai Intervening Variabel pada Produk Kosmetik dan Perawatan Wajah. JIMMU. Volume III- Nomor 1.Rahmi, Y, & Sekarsih, L. 2017. The Influence of Beauty Vlog on Perceived Source Credibility and Purchase Intention. Makara Hubs-Asia, 21(1): 13-23.Ruhamak, M.Dian & Rahayu, Budi. 2016. Pengaruh Word Of Mouth Terhadap Purchase Intention melalui Brand Image pada Lembaga Kursus Bahasa Inggris Dynamic English Course Pare. Jurnal Ekonomi Universitas Kadiri. Vol. 1, No. 2, 188 â€“ 204Sabdosih, Zakiya. 2013. Pengaruh Variabel Celebrity Endorser terhadap Citra Merek Lâ€™oreal (Studi Produk Lâ€™oreal Paris Total Repair di Fakultas Ekonomi dan Bisnis Universitas Brawijaya Malang. Jurnal Ilmiah Mahasiswa FEB Vol 1, No.2Schiffman, Leon & Kanuk, Leslie Lazar. 2010. Perilaku Konsumen. Jakarta: PT Indeks.Setiadi, Nugroho J. 2013. Perilaku Konsumen Perspektif Kontemporer pada Motif, Tujuan, dan Keinginan Konsumen. Jakarta: PT. Kharisma Putra Utama.Shimp, Terence A., 2002. Periklanan promosi : aspek tambahan komunikasi pemasaran terpadu; Jilid I. Jakarta: Erlangga.Sinaga, R.E.M & Kusumawati, A. 2018. Pengaruh Youtube Beauty Vlogger Terhadap Minat Beli Konsumen dan Dampaknya Terhadap Keputusan Pembelian Produk (Studi pada Pengguna Kosmetik Maybelline di Indonesia). Jurnal Administratsi Bisnis (JAB). Vol. 63 No. 1Solimun., Fernandes, A. A. R., Nurjannah. 2017. Metode Statistika Multivariat: Pemodelan Persamaan Struktural (SEM). Malang: UB Press.Stefani, Selfi. 2013. Analisis Pengaruh Iklan Televisi, Celebrity Endorser, Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian pada Produk Kosmetik Berlabel Halal Wardah. Skripsi Fakultas Ekonomi dan Bisnis Universitas Islam Negeri Syarif Hidayatullah.Sugiyono. 2016. Metode Penelitian Kuantitatif Kualitataif dan Kombinasi (Mixed Methods).Bandung: Alfabeta.Sujana, Made Shinta Ayu Saraswati & Giantari, I Gusti Ayu Ketut. 2017. Peran Brand Image Memediasi Celebrity Endorser dengan Purchase Intention. Forum Keuangan dan Bisnis Indonesia (FKBI), Vol. 6Sunarti, Wibowo, Edi & Utami, Setyaningsih Sri. 2019. Pengaruh Beauty Vlogger Terhadap Minat Beli Produk Kosmetik Wardah dengan Citra Merek sebagai Variabel Mediasi (Survei pada Mahasiswa Universitas Slamet Riyadi Surakarta). Jurnal Ekonomi dan Kewiraushaan Vol. 19 No. 4.Thusyanthy, Vadivelu & Tharanikaran, Vadivelu. 2015. The Relationship Variables to Celebrity Endorsement and Brand Equity A Comprehensive Review. Journal of Business and Management, 10 (11): pp: 212-221